Terrestrial Snails Affecting Plants in Florida - John L. Capinera; Jodi White (EDIS)
Most snails are either beneficial or harmless, but a few snails may feed on economically important plants and become pests. The terrestrial species that can become plant pests are discussed in this 12-page fact sheet written by John L. Capinera and Jodi White, and published by the UF Department of Entomology and Nematology, July 2011.